STRATEGI DAKWAH KYAI AHMAD DARDIRI S.Pd. DALAM MENYIARKAN AGAMA ISLAM PADA MASYARAKAT DESA CENDORO - Khofifah Indrian Nurlaili; Aflachal Muthowah (Universitas Kiai Abdullah Faqih (UNKAFA) Gresik, 2022)
The approach used in this study is a qualitative approach, because this approach is used to explore the da'wah strategy carried out by Kyai Ahmad Dardiri S.Pd in carrying out da'wah to the people of Cendoro Village. Therefore, this research process is expected to produce descriptive data in the form of written or oral data from the people or behavior observed to provide an explanation of what Kyai Ahmad Dardiri S.Pd da'wah strategies are. as well as the supporting and inhibiting factors of his da'wah strategy. The results showed that although Kyai Ahmad Dardiri S.Pd. with less than perfect physical conditions, the process is still hampered by various inhibiting factors and various supporting factors. However, Kyai Ahmad Dardiri S.Pd with his persistent struggle he used 2 strategies, namely: sentimental strategy and rational strategy. While the method also uses 2 methods, namely: oral bill and hal. In each of his preaching, Kyai Dardiri always inserts materials experienced by the people of Cendoro Village, so that many of them are moved to listen to the recitations conducted by Kyai Ahmad Dardiri S.Pd. Kata kunci: Da’wah, Kyai, Metode